Relationship between measures of thoracic diameter and cardiopulmonary resuscitation-induced thoracoabdominal injury - Ümit,Tuba Betül (2022)
SUMMARY OBJECTIVE: We investigated the relationship between thoracic diameters and chest compression-related thoracoabdominal injury in patients with non-traumatic out-of-hospital cardiac arrest who had a return of spontaneous circulation after cardiopulmonary resuscitation. METHODS: A total of 63 consecutive adult non-traumatic out-of-hospital cardiac arrest patients were enrolled in this prospective study. Computed tomography was performed on each patient and the anteroposterior diameter, skin-to-skin anteroposterior diameter, and transverse diameter of the chest were measured. Patients were divided into two groups based on the presence or absence of cardiopulmonary resuscitation-related thoracoabdominal injury. Age, sex, and duration of cardiopulmonary resuscitation, anteroposterior diameter, skin-to-skin anteroposterior diameter, and transverse diameter were compared between the groups. The primary outcome was the relationship between thoracic diameters and cardiopulmonary resuscitation-induced thoracoabdominal injuries. RESULTS: Thoracoabdominal injuries were detected in 46% (n=29) of the patients and consisted of rib fractures in 22 (34.9%) patients, pulmonary contusion in 7 (11.1%), and sternal fracture in 3 (4.8%) patients. There were no significant differences in cardiopulmonary resuscitation duration between patients with and without thoracoabdominal injuries (p=0.539). Similarly, there were no significant differences in anteroposterior diameter, skin-to-skin anteroposterior diameter, or transverse diameter between patient groups (p=0.978, p=0.730, and p=0.146, respectively) or between patients who died within the first 28 days and those who survived for longer than 28 days (p=0.488, p=0.878, and p=0.853, respectively). CONCLUSION: The iatrogenic thoracoabdominal injuries caused by cardiopulmonary resuscitation performed according to the cardiopulmonary resuscitation guidelines were independent of thoracic diameters. Therefore, the cardiac compression depth of 5–6 cm recommended by the current cardiopulmonary resuscitation guidelines is reliable for patients with different thoracic diameters.